SnS/LDPE Composite: A reusable floating photocatalyst for solar degradation of organic dyes. (2021) - Hegde, S.S.; Surendra, B.S.; Priyanka, V.P.; Murahari, Prashantha; Ramesh, K.
Highlights: Floating SnS/LDPE photocatalysts synthesized and tested for MB dye degradation under direct sunlight. The partially submerging 40 wt% SnS/LDPE catalyst showed superior degradation efficiency of 93%. Incorporation of 20 wt% of Fe3 O4 into SnS/LDPE makes the catalyst magnetically separable. Features of SnS/LDPE composite photocatalyst are practical in treating dying industry waste water using solar energy. Abstract: Stable and reusable floating photocatalysts are highly sought-after for the complete utilization of the solar radiation in real industrial waste water treatment. Solar radiation responsive low-density polyethylene (LDPE)/SnS composite floating photocatalysts were prepared by embedding 20 wt% to 50 wt% of SnS nanoparticles into LDPE matrix. The photocatalytic activities of the composites were examined for the degradation of Methylene blue (MB) dye under direct sunlight irradiation with no mechanical stirring and oxygenation. The composite with 40 wt% SnS in LDPE, with a density of 1.005 g cm −3 partially submerged and showed superior degradation efficiency of 93% by facilitating efficient illumination and oxygenation. The near floating nature of the 40 wt% SnS/LDPE composite makes it of a great advantage for easy recollecting and re-using in actual waste water treatment of dying industry. The optical microscopy revealed discontinuous-porous structure for the composite with higher wt.% of SnS, causing increased active surface area. Incorporation of 20 wt% of Fe3 O4 into SnS/LDPE composite makes the catalyst magnetically separable. Photocatalytic activity of novel SnS with cubic crystal structure is also tested. FTIR analysis of MB revealed the catalytic activity of SnS/LDPE composite and reaction path of dye degradation. The developed photocatalysts are stable and their photocatalytic activity was found to be sustained after five consecutive runs. The studied catalytic material will have real practical application in treating dyeing industry waste water economically by using low-cost SnS and naturally available solar radiation.